‘A minor atlantic Goethe’: W.H. Auden’s Germanic bias - Arnold, H (2014)
This thesis is an account of the poet and critic W.H. Auden's relations with Germany and Germans over the course of his life (1907-1973), presented through a selection of influences that have received little critical attention in the corpus of secondary literature to date. While these connections and influences are manifold and sometimes disparate, they can serve as a prism to tell Auden's life-story from a particular, relatively unexplored angle and to illuminate his work. The thesis is divided into three chapters. Chapter One discusses Auden’s engagement with German literature before 1928, his reasons for spending nine months in Weimar Berlin 1928-29, and the formative influence of this experience on his life and work. Chapter Two explores Auden's relationship with his 'in-laws', the famous family of Nobel Prize winning author Thomas Mann, and Auden's choice of an international life-style. Chapter Three discusses various other, later German influences on Auden: his visit to Germany with the US Army and its traces in The Age of Anxiety; issues concerning the German translation of this text; his Ford Foundation residence in isolated West Berlin; and his intellectual friendship with Hannah Arendt. Introduction and Conclusion embed these three specific chapters, deliberating the topic more abstractly. A number of appendices bring together a wide range of unpublished sources – and their translations into English, if the original is composed in German. Translations of all German appendix material can be found in the appendix itself.